THE EFFECT OF THIN CAPITALIZATION ON TAX AVOIDANCE WITH COMPANY SIZE AS A MODERATION VARIABLE: PENGARUH THIN CAPITALIZATION TERHADAP PENGHINDARAN PAJAK DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Apriansyah Sarif; Surachman Surachman (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
This study aims to determine the effect of thin capitalization on tax avoidance. In addition, this study also aims to determine the effect of firm size in moderating the relationship between thin capitalization and tax avoidance. This research was conducted at the Pharmaceutical Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 Period. The method used in this study is a quantitative method using secondary data in the form of financial statements and annual reports. The population used in this study amounted to 10 pharmaceutical companies listed on the IDX. The sample in this study was selected using the saturated sample method, so that 50 samples or 10 companies were obtained for 5 years. Data analysis in this study uses the moderate regression analysis method with a statistical program tool, namely SPSS Version 26. The results of hypothesis testing, it shows that partially (1) Thin Capitalization has a significant effect on Tax Avoidance and in moderation (2) Thin Capitalization has no effect on Tax Avoidance. The conclusion of this study is that partially Thin Capitalization has a significant effect on tax avoidance and Firm Size as a moderating variable weakens the effect of Thin Capitalization on Tax Avoidance